2022
DOI: 10.1186/s13047-022-00568-x
|View full text |Cite
|
Sign up to set email alerts
|

What do we actually know about a common cause of plantar heel pain? A scoping review of heel fat pad syndrome

Abstract: Background The heel fat pad is an important structure of the foot as it functions as a cushion to absorb shock and distribute plantar force during ambulation. Clinical practice guidelines or decision support platforms emphasize that heel fat pad syndrome (HFPS) is a distinct pathology contributing to plantar heel pain. We aimed to identify and synthesize the prevalence, etiology and diagnostic criteria, and conservative management of HFPS. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Some patients sustain symptoms for more than one year and experience intractable plantar fasciitis. Numerous risk factors, such as aging, obesity, repetitive injury, or prolonged stimuli, may attribute to these chronic symptoms [4][5][6]. Relieving symptoms quickly is important because plantar fasciitis reduces quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients sustain symptoms for more than one year and experience intractable plantar fasciitis. Numerous risk factors, such as aging, obesity, repetitive injury, or prolonged stimuli, may attribute to these chronic symptoms [4][5][6]. Relieving symptoms quickly is important because plantar fasciitis reduces quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria included patients (1) who declined to participate in the study; (2) with heel pain for any other reason, including a calcaneal stress fracture, infection, tumors, rheumatic enthesopathy, or nerve entrapment; (3) with disorders of the foot or ankle not related to plantar fasciitis; (4) who had received any other injection including steroids in the past 3 months; (5) with systemic diseases or any severe diseases of the heart, liver, or kidney; and (6) with a history of alcohol, drug abuse, or psychiatric history [19].…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of our participants complained about pain or reported any injury. Therefore, these findings raise intriguing questions regarding how this energy is utilized by the body or dissipated by the foot and if excessive energy dissipation is associated with tissue mechanical properties like thickness and stiffness and contributes to foot complications like plantar heel pain [ 62 ]. Nevertheless, our study showed that downhill walking exaggerated the dissipative behavior of the healthy foot during the entire and early phase of each step, suggesting that the foot contributes to the dissipation of impacts by the legs during downhill walking [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistics indicate that around 7% of individuals aged 65 and above report experiencing discomfort in the heel region. Furthermore, identification and management of this pain originating from the plantar area contribute to over a million medical visits annually in India (1,2) . Patients commonly describe experiencing pain at the front-inner part of the heel bone.…”
Section: Introductionmentioning
confidence: 99%